Antioxidant Activities and Quantification of Carotenoids, Phenolics, and Flavonoids in the Methanolic Extract of the Marine Microalga Odontella sp. - Machana, Kwanchayanawish; Amonrat; Sutthanut, Khaetthareeya; Thumanu, Kanjana; Thumpitak, Anusorn; Rittirod, Theera; Jadprakob, Chonlada; Phadungkit, Methin; Hongthong, Jakkrit; Kaewnopparat, Nattha (Health Science Journal of Nakhon Ratchasima College, 2025)
The marine microalgae group diatoms (Odontella sp.) are brown microalgae belonging to the Bacillariophyta, found in the sea along the eastern coast of Thailand. They have the potential to be developed as components of dietary supplements and health products due to their various important chemical constituents. Therefore, this research investigates the antioxidant activities and quantifies the carotenoid compounds in the methanol extract of the marine algae Odontella sp. using HPLC techniques. Additionally, the total phenolic content (TPC) and total flavonoid content (TFC) were analyzed to evaluate their correlation with antioxidant activities. The study found that the methanol extract of the marine microalgae Odontella sp. had IC50 values from antioxidant activity tests using the DPPH and ABTS methods of 0.910 ± 0.04 µg/ml and 0.057 ± 0.04 µg/ml, respectively. Additionally, the TPC and TFC were found to be 18.9±0.7 gram GAE per 100 gram extract and 17.5±0.6 gram QE per 100 gram extract, respectively. HPLC analysis revealed the presence of carotenoid compounds, including astaxanthin, canthaxanthin, and fucoxanthin, but zeaxanthin was not detected. All the compounds are associated with the antioxidant activities of the extract. Therefore, the results of this study support that the extract from Odontella sp. has the potential to be developed into dietary supplements or utilized in nutrition and anti-aging applications in the future.